A Desaign of Caffeate Acid Derivatives for Anticancer based on DFT Molecular Docking: Studi Senyawa Turunan Asam Kafeat sebagai Antikanker: Pendekatan DFT dan Molecular Docking - Oksal, Efriyana; Ariefin, Mokhamat; Pasaribu, Marvin Horale (Jurnal Jejaring Matematika dan Sains, 2023)
This research informs a descriptive study of caffeic acid derivatives such as ethyl caffeate, fluoro methyl caffeate, chloro methyl caffeate, bromo methyl caffeate, iodo methyl caffeate compounds, using density functional theory in B3LYP method with def2-TZVP basis set. The substitution of various halide atoms in the derivative compounds showed a high increase in chemical reactivity than the methyl group for the main compound by increasing the electron donor ability of the compound in chemical reactions. The molecular structures of some derivative compounds were optimized with geometrical analysis values depicting stable molecular structures with lower HOMO-LUMO energy difference. Quantum chemical parameters such as hardness (η), softness (σ), electronegativity (χ), and electrophilicity (ω) were generated as descriptors for the chemical behavior of the molecules. The FT-IR vibrational frequencies that have been calculated and characterized are in good agreement with the molecular structure. The molecular docking results show that the five ligands are able to interact with amino acid residues similar to the amino acids of the native ligand. The binding energy values for the five native ligands are -6.5, -6.8, -6.6, -6.5, and -6.4 kcal mol-1. Furthermore, binding and interaction values similar to the native ligand, it is expected that the five ligands have potential as anticancer.